In vitro anti-cancer activity of Doxycycline on some human cancer cell lines - ALMhana, Nadia Matter (Iraqi Journal of Cancer and Medical Genetics, 2016)
Doxycycline (DC) is an antibiotic that is used in the treatment of number types of infections diseases caused by bacteria and protozoa. Doxycycline is a kind of second-generation tetracyclines which is commonly used to treat a variety of infections. Three cancer cell lines include: human cerebral glioblastoma-multiforme (AMGM) at passages 75-84, human cervical cancer (HeLa) at 70 passages, and human pelvic rhabdomyosarcoma (RD) at 75 passages cell lines were used in this study. The results showed that DC exerted significant cytotoxic effects with all concentrations used (50,100,150,200,250,300,350 and 400) µg/ml on all types of cell lines. Because of cytotoxic activity, good pharmacokinetic characteristics and the safety of drug which used for many years in the treatment of infectious disease, we can conclude that these characteristics make DC a valuable treatment for many types of cancer.